Perbedaan Generasi Pada Hubungan Kinerja Dan Motivasi Kerja Karyawan Di PT. HM Sampoernaarea Bengkulu - Nurdianto Nurdianto; Fahrudin Js Pareke; Nasution Nasution (Student Journal of Business and Management, 2023)
The existence of the phenomenon of several work forces and based on several different generational theories makes it an interesting thing to study. This is based on the phenomenon that many companies currently have employees with different generations. The purpose of this study is to describe the level of performance and motivation between generations. This study uses two variables, namely performance and motivation. Performance variables use task, adaptive and contextual indicators while motivational variables are measured by intrinsic and extrinsic indicators. Collecting data using a questionnaire to 108 respondents who work at PT. HM Sampoerna Bengkulu. To see the relationship between the two variables, this study used the one-way ANOVA test. The results of the analysis on performance variables and work motivation between generations show a significant relationship, it is concluded that employee performance has a high value, meaning that performance increases, indicating good work results. Variable employee motivation between generations has a very high value. This means the high work motivation of employees then the performance is increasing. The performance of employees between generations has significant differences in generations X, Y and Z which shows that the higher the performance, the better the work will be. Employee motivation has been shown to have significant differences in intergenerational performance, indicating that differences in generational ability produce good performance in the presence of motivation.